Biomarkers of subclinical atherosclerosis in patients with psoriatic arthritis - Peluso R (Dove Medical Press, 2019)
Rosario Peluso,1 Francesco Caso,1 Marco Tasso,1 Vincenzo Sabbatino,1 Roberta Lupoli,2 Matteo Nicola Dario Di Minno,3 Francesco Ursini,4 Luisa Costa,1 Raffaele Scarpa1, On behalf of CaRRDs study group1Department of Clinical Medicine and Surgery, Rheumatology Research Unit, Federico II University, Naples, Italy; 2Department of Clinical Medicine and Surgery, Division of Internal Medicine, Federico II University, Naples, Italy; 3Department of Advanced Biomedical Sciences, Division of Cardiology, Federico II University, Naples, Italy; 4Internal Medicine Unit, Department of Medical Sciences, University of Ferrara, Ferrara, ItalyBackground: Psoriatic arthritis (PsA) is a chronic immune-mediated disease. It is associated with an increase in cardiovascular risk factors (obesity, hypertension, diabetes, and dyslipidemia), giving a higher risk of major adverse cardiovascular events. Patients with PsA have an increased incidence of subclinical atherosclerosis and endothelial dysfunction. The aim of this study is to perform a review of the biomarkers of subclinical atherosclerosis in patients with PsA.Methods: A search was performed in the electronic databases (PubMed, Web of Science, Scopus, and Embase) up until July 2017. Studies were considered if they included data on biomarkers of subclinical atherosclerosis in PsA, and each article was then reviewed for quality and clinical relevance. After completing the literature search, all screened literature was summarized and discussed in our study group (CaRRDs study group).Results: The initial search produced 532 abstracts, which were limited to 258 potentially relevant articles by preliminary review of the titles and by excluding review articles and case reports (n=274). A further 102 articles were deemed ineligible after examining the abstracts. Full texts of the remaining 156 articles were retrieved. Most articles were excluded because they were not relevant to the biomarkers of subclinical atherosclerosis in psoriasis and/or PsA. In the end, 54 articles were deemed eligible for this review.Conclusion: Patients with PsA showed more severe atherosclerotic disease compared with patients with only psoriasis. This may have been due to the higher systemic inflammatory burden from the combination of both diseases. In patients with PsA some molecules may be considered as markers of atherosclerotic disease, and their detection may be a prognostic marker, in addition to imaging procedures, for the development of atherosclerotic disease, and could be suitable for the management of patients with PsA.Keywords: psoriatic disease, insulin resistance, lipid profile, serum uric acid, complement C3, primary and secondary hemostasis